Analisis Indeks Masa Tubuh, Panjang Lengan, Power Lengan, Vo2max, dan Kelincahan pada Atlet Judo - Iwandana, Dody Tri; Zubaida, Ida; Nugroho, Wildan Alfia; Utami, Danarstuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study analyzed body mass index, arm length, VO2 max arm power, and agility in judo athletes. This type of research is quantitative descriptive research. This research method analyzes the physical condition of judo athletes—and indicators of success in program implementation. The population used in this research was 23 judo athletes from Bantul Regency. The research results show that the average height was 167.60 cm, including the medium category. The average body weight was 65.08 kg, including the medium category. The average leg length was 88.60 cm, including the medium category; the average arm length was 68 86 cm in the medium category; the average coordination test was 8.13 times, it is in the medium category. The average side step agility is 14.78 times, which is in the medium category; the average leg power is 44.78 cm, which is in the medium category; the average power arm is 5.54 times, including the medium category, and the average VO2max 7.91 mol/kg is/min including the medium category. The conclusion is that the height, weight, leg length, arm length, hand-eye coordination, agility, leg power, arm power, and endurance of Bantul Regency judo athletes are in the medium category. Keywords: Analysis, Athlete, Physical Condition, Judo